Improvements in Balance in Older Adults Engaged in a Specialized Home Care Falls Prevention Program - Whitney, Susan L. (J Geriatr Phys Ther, 2013)
BACKGROUND AND PURPOSE: To determine if persons older than 65 years receiving a combination of physical therapy, occupational therapy, speech, or nursing interventions in their home demonstrated changes in gait/balance function after an episode of home care services. METHODS: Charts from 11 667 persons who were at risk for falling and who were participating in an exercise program in the home were included. STUDY DESIGN: Data were retrieved from the Outcome and Assessment Information Set, Version B, and the computerized database of physical therapist–collected outcome data. Recorded physical therapist–data may have included a neuropathic pain rating, the Berg Balance Scale (BBS), the Performance Oriented Measurement Assessment (POMA), the Dynamic Gait Index (DGI), and the modified Clinical Test of Sensory Integration and Balance (mCTSIB). DATA ANALYSIS: Data were extracted by an honest broker and were analyzed. Mean (SD) change in each performance test and the percentage of participants in the total sample and in the 9 age/health condition strata that exceeded the minimum detectable change (MDC) for each gait/balance measure were described. The value of MDC95 describes the amount of true change in participant status beyond measurement error with 95% certainty. RESULTS: The gait/balance measures demonstrated MDCs ranging between 68% and 91% for the study sample. Mean (SD) of improvement on the BBS was 12 (8) points, with 88% of all participants exceeding the BBS MDC95 value of 5 points. Mean (SD) of improvement in gait/balance performance as measured by the POMA was 8 (4) points, with 91% of all participants exceeding the POMA MDC95 value of 3 points. Among all patients, mean (SD) of improvement on the DGI was 7 (4) points with 91% of all participants exceeding the DGI MDC95 value of 2 points by discharge. At admission, the median number of mCTSIB conditions that could be completed was 1 and the median number of completed conditions on the mCTSIB increased to 3 at discharge, with 81% of all participants demonstrating improvement. CONCLUSION: On the basis of established criteria, participants seemed to make clinically meaningful gains after the home care episode of care.